Binary Liquid Crystal Mixtures Based on Schiff Base Derivatives with Oriented Lateral Substituents - Rua B. Alnoman; Mohamed Hagar; Hoda A. Ahmed; Magdi M. Naoum; Hanefah A. Sobaih; Jawaher S. Almshaly; Mawadh M. Haddad; Rana A. Alhaisoni; Tahani A. Alsobhi (Crystals, 2020)
Binary mixtures of the laterally substituted Schiff base/ester derivatives, namely 4-((2- or 3-) substituted phenyl imino methyl) phenyl-4”-alkoxy benzoates, Ia–d, were prepared and mesomorphically studied by differential scanning calorimetry (DSC) and their mesophases identified by polarized optical microscopy (POM). The lateral group (1-naphthyl, 2-F, 2-Br, 3-F in Ia–d, respectively) is attached to different positions of the phenyl Schiff moiety. The mixtures investigated were made from two differently shaped compounds that differ from each other in the polarity, size, orientation, and relative positions of the lateral group. The results revealed that the binary mixture Ia/Ib (bearing the naphthyl and 2-flouro substituents) exhibited the SmA phase, which covered the whole composition range. For the mixtures Ib/Id (2-F and 2-Br), the isomeric lateral F-group in compound Ib distributed the SmA arrangement of Id. In the Ic/Id mixture bearing two positionally and structurally different substituents, the addition of Ic to Id resulted in solid binary mixtures where its behavior may be attributed to the negligible steric effect of the small electronegative fluorine atom compared to the Br atom. Density functional theory (DFT) theoretical calculations were carried out to estimate the geometrical parameters of individual components and to show the effect of these parameters in the mesophase behavior of the binary system, where the higher dipole moment of Id (6 Debye) may be the reason for its high π–π molecular stacking, which influences its mesophase range and stability.